Ultimate Eocene (Priabonian) chondrichthyans (Holocephali, Elasmobranchii) of Antarctica - Kriwet, Jürgen (2016)
The Eocene La Meseta Formation on Seymour Island, Antarctic Peninsula, is known for its remarkable wealth of fossil remains of chondrichthyans and teleosts. Chondrichthyans seemingly were dominant elements in the Antarctic Paleogene fish fauna, but decreased in abundance from middle to late Eocene, during which time remains of bony fishes increase. This decline of chondrichthyans at the end of the Eocene generally is related to sudden cooling of seawater, reduction in shelf area, and increasing shelf depth due to the onset of the Antarctic thermal isolation. The last chondrichthyan records known so far include a chimeroid tooth plate from TELM 6 (Lutetian) and a single pristiophorid rostral spine from TELM 7 (Priabonian). Here, we present new chondrichthyan records of Squalus, Squatina, Pristiophorus, Striatolamia, Palaeohypotodus, Carcharocles, and Ischyodus from the upper parts of TELM 7 (Priabonian), including the first record of Carcharocles sokolovi from Antarctica. This assemblage suggests that chondrichthyans persisted much longer in Antarctic waters despite rather cool sea surface temperatures of approximately 5°C. The final disappearance of chondrichthyans at the Eocene–Oligocene boundary concurs with abrupt ice sheet formation in Antarctica. Diversity patterns of chondrichthyans throughout the La Meseta Formation appear to be related to climatic conditions rather than plate tectonics.